A Tale of Loops and Tails: The Role of Intrinsically Disordered Protein Regions in R-Loop Recognition and Phase Separation - Dettori, Leonardo G.; Torrejon, Diego; Chakraborty, Arijita; Dutta, Arijit; Mohamed, Mohamed; Papp, Csaba; Kuznetsov, Vladimir A.; Sung, Patrick; Feng, Wenyi; Bah, Alaji (Frontiers in Molecular Biosciences, 2021)
R-loops are non-canonical, three-stranded nucleic acid structures composed of a DNA:RNA hybrid, a displaced single-stranded (ss)DNA and a trailing ssRNA overhang. To elucidate their cellular functions, we need to understand the mechanisms underlying R-loop formation, recognition and resolution. Previous high-throughput screens identified proteins that bind R-loops, with many of these proteins containing folded nucleic acid binding and enzyme domains that prevent deleterious R-loop accumulation. However, a significant number of these R-loop Enzymes and Readers also contain intrinsically disordered regions (IDRs). The precise structural mechanisms by which the folded domains and IDRs synergize to process R-loops or modulate signaling have not been fully explored. While studying one such modular R-loop Reader, the Fragile X Protein (FMRP), we discovered that the C-terminal IDR (C-IDR) is the predominant R-loop binding site. Interestingly, the C-IDR of FMRP has recently been shown to undergo spontaneous Liquid-Liquid Phase Separation (LLPS) assembly by itself or in complex with another non-canonical nucleic acid structure, RNA G-quadruplex. Furthermore, we have recently shown that FMRP can suppress persistent R-loops that form during transcription, a process that is also enhanced by LLPS via the assembly of membrane-less transcription factories. These exciting findings prompted us to explore the role of IDRs in R-loop processing and signaling proteins through a comprehensive bioinformatics and computational biology study. Here, we evaluated IDR prevalence, sequence composition and LLPS propensity for the known R-loop interactome. We observed that, like FMRP, the majority of the R-loop interactome, especially Readers, contains long IDRs that are highly enriched in low complexity sequences with biased amino acid composition, suggesting that these IDRs could directly interact with R-loops, rather than being ‘mere flexible linkers’ connecting the ‘functional folded enzyme or binding domains’. Furthermore, our analysis shows that several proteins in the R-loop interactome are either predicted to or have been experimentally demonstrated to undergo LLPS or are known to be associated with phase separated membrane-less organelles. Thus, our overall results present a thought-provoking hypothesis that IDRs in the R-loop interactome can provide a functional link between R-loop recognition via direct binding and downstream signaling through the assembly of LLPS-mediated membrane-less R-loop foci.